Pemanfaatan Data Penginderaan Jauh Untuk Pemetaan Tingkat Kerawanan Kebakaran Hutan Di Kabupaten Rokan Hilir Tahun 2022 - Rafliando, M Aryasatya; Kusumawati, Lia; Ramadhoan A, Fauzi (Peneliti.net, 2024)
This The world of remote sensing in the digital era can utilize various types of the latest technology to identify various phenomena in a more modern way. With fire disasters increasing again after the pandemic is over, it is necessary to update spatial information about the level of vulnerability to fire disasters in Indonesia. Therefore, this research aims to map the level of vulnerability to forest fires in Rokan Hilir Regency using remote sensing data in 2022. This research uses quantitative methods. Data processed through processesWeighted overlay to carry out weighting on parameters that have been classified according to the level of vulnerability. The parameters used include surface temperature, rainfall, hot spots, land cover, distance from road, and distance from river. The results of this research are a map of the level of vulnerability to forest fires in Rokan Hilir Regency with five classifications of vulnerability, namely very low, low, medium, high and very high. Based on the research results, the percentage of vulnerability levels is dominated by the